2012
DOI: 10.1152/ajpcell.00443.2011
|View full text |Cite
|
Sign up to set email alerts
|

ZnT4 provides zinc to zinc-dependent proteins in the trans-Golgi network critical for cell function and Zn export in mammary epithelial cells

Abstract: McCormick NH, Kelleher SL. ZnT4 provides zinc to zincdependent proteins in the trans-Golgi network critical for cell function and Zn export in mammary epithelial cells. Am J Physiol Cell Physiol 303: C291-C297, 2012. First published May 23, 2012 doi:10.1152/ajpcell.00443.2011 transporter 4 (ZnT4) plays a key role in mammary gland Zn metabolism. A mutation in ZnT4 (SLC30A4) that targets the protein for degradation is responsible for the "lethal milk" (lm/lm) mouse phenotype. ZnT4 protein is only detected in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 41 publications
5
46
0
Order By: Relevance
“…FluoZin-3 Assay-Transfected HC11 MECs were loaded with FluoZin-3 (Toronto Research Chemicals Inc., Ontario, Canada) as previously described (24) and were viewed by livecell imaging on the Leica Inverted Confocal Microscope SP8 (Leica Microsystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FluoZin-3 Assay-Transfected HC11 MECs were loaded with FluoZin-3 (Toronto Research Chemicals Inc., Ontario, Canada) as previously described (24) and were viewed by livecell imaging on the Leica Inverted Confocal Microscope SP8 (Leica Microsystems).…”
Section: Methodsmentioning
confidence: 99%
“…Because women with mutations in ZnT2 have a much greater (50 -90%) reduction in milk zinc concentration (10,11,13,16,17), we expected to see a greater loss of zinc transfer into milk in ZnT2ko mice. Given this unexpected finding, we tested the hypothesis that ZnT4 expression was augmented to compensate for the lack of ZnT2, as we and others (24,46) have shown that ZnT4 is important for zinc secretion into milk. However, we found that ZnT4 abundance was actually lower in the mammary glands from ZnT2ko mice (data not shown), eliminating a compensatory response as an alternative explanation.…”
Section: Znt2-null Mice Have Defects In Subcellularmentioning
confidence: 99%
“…In general, Zn 2+ transport is regulated by ZnT (also known as solute carrier family 30) and ZIP (also known as solute carrier family 39) transporters, and it is chelated by Zn 2+ -binding metallothioneins. In addition to Zn 2+ evacuation across the plasma membrane by the Zn 2+ transporter ZnT1 (SLC30A1) (Palmiter and Findley, 1995), Zn 2+ is exported from the cytoplasm into the organelles by the dedicated ZnT transporters such as ZnT6 (SLC30A6) for the Golgi (Huang et al, 2002), and ZnT2 (SLC30A2) and ZnT4 (SLC30A4) for the lysosome (Palmiter et al, 1996;Huang and Gitschier, 1997;Falcón-Pérez and Dell'Angelica, 2007;McCormick and Kelleher, 2012). This organellar Zn 2+ export lowers potentially toxic cytoplasmic Zn 2+ concentrations in pathophysiological conditions such as neurodegeneration (Kanninen et al, 2013) and breast cancer .…”
Section: Cellular Znmentioning
confidence: 99%
“…Furthermore, HC11 cells have been applied to examine the impact of toxic compounds on lactating mammary cells (Öhrvik et al 2010) and also to characterize some transporters belonging to the Solute Carrier (SLC) family and ion channels, which are implicated in the flux of magnesium, zinc, copper, and calcium across the membranes of the lactating mammary epithelium Lönnerdal 2005, 2006;Boyd and Náray-Fejes-Tóth 2007;Öhrvik et al 2010;Wolf et al 2010;McCormick and Kelleher 2012;Ross et al 2013). However, the HC11 cell model has not yet been used to characterize expression and/or function of ATP Binding Cassette (ABC) transporters.…”
Section: Discussionmentioning
confidence: 99%
“…The HC11 cells express functional prolactin receptors and have been used as a model to examine the progression of mammary epithelial differentiation to a secreting phenotype (Ball et al 1988;Marte et al 1994;Desrivières et al 2003). In addition, the HC11 cell model has been applied to characterize transporters implicated in the flux of zinc, copper, sodium, and calcium across the membranes of the lactating mammary epithelium Lönnerdal 2005, 2006;Boyd and Náray-Fejes-Tóth 2007;Öhrvik et al 2010;McCormick and Kelleher 2012;Ross et al 2013). However, no studies have so far been directed to investigating expression and function of ABC transporters in HC11 cells.…”
Section: Introductionmentioning
confidence: 99%